American Indian women cancer survivors' coping with depressive symptoms. Issue 4 (4th July 2019) - Burnette, Catherine E.; Roh, Soonhee; Liddell, Jessica; Lee, Yeon-Shim
Abstract: Objective: Depressive symptoms have been identified as a primary predictor of quality of life among cancer patients. Depression and cancer are co-occurring and disproportionately elevated for American Indian and Alaska Native (AI/AN) women. The purpose of this article is to examine American Indian (AI) women cancer survivors' coping mechanisms for depressive symptoms. Research approach: The methodology included a qualitative descriptive approach with conventional content analysis to examine the coping strategies of AI women cancer survivors associated with depressive symptoms. The interview guide was semi-structured and developed in collaboration with a community advisory board (CAB). Data-derived qualitative analysis was used to generate codes inductively from the data. Participants: A sample of 43 AI women cancer survivors ( n = 14 cervical cancer, n = 14 breast cancer, and n = 15 other cancers) from the Northern Plains region, in the state of South Dakota were interviewed. Data were collected from June 2014 to February 2015. Methodological approach: Qualitative content analysis was used for data analysis, which allowed themes to emerge inductively from the data. Analysis revealed 430 preliminary codes. After de-briefing, validation, and discussion among coauthors, these were then sorted into 67 codes. Member checks with all available participants were conducted to minimize misinterpretation. Findings: A total of 26 participants (62%) indicated they had feelings of depression since their cancer diagnosis. Women coped with depressive feelings by (a) participating in faith traditions; (b) seeking creative and positive outlets; (c) martialing family and social support; and (d) keeping busy with other life activities. Interpretation: AI women experienced depressive symptoms following a cancer diagnosis and used a variety of positive coping mechanisms to create personal meaning. Implications for Psychosocial Providers or Policy: AI women may need unique support following a cancer diagnosis, and interventions should incorporate AI beliefs and traditions, such as storytelling and talking with family and community members.